System of acquisition of information for measurement of radioelectric parameters in linear antennas in the band of VHF and UHF’s television (2007)
This project develops a data acquisition and processing system for the measurement and adjustment of radioelectric parameters of linear antennas in the VHF and UHF bands. As a test signal, some of the television signals found in the radio spectrum are used, coming from transmitters that broadcast signals from national channels. The implemented receiver includes a commercial television tuner that takes the video carrier signal as a sample. This signal is amplified, filtered, stored and conditioned, to be read by the serial port of a personal computer and processed using a program in Visual Basic, with a graphical interface that allows a user-friendly interaction. From here you interact with a microcontroller that controls the positioning mechanism of the receiving antenna through an electromechanical structure, which allows you to execute movements in two degrees of freedom: in azimuth and elevation. This achieves a system capable of automatically determining the optimal aiming of the antenna according to the maximum level of signal reception. Likewise, the antenna's own parameters are determined such as: the radiation pattern (both in the horizontal and vertical plane), the directive gain of the antenna, the gain in each of the points that make up the main plane, and others parameters of interest for the analysis of the real characteristics of linear antennas.